146k views
1 vote
Replace the values of h and k to create the equation of the transformed function.

Replace the values of h and k to create the equation of the transformed function.-example-1

1 Answer

4 votes

Answer:

  • h = 4 and k = 1

Explanation:

y = ∛x is the original function, which has its center in the origin

As we see the function y = ∛(x - h) - x has its center moved to the point (4, -1)

This gives us h = 4 and k = 1, as negative h indicates translation to the right and negative k- translation down

Replace the values of h and k to create the equation of the transformed function.-example-1
User AKor
by
6.1k points